2010
DOI: 10.1177/1403494809357259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of socioeconomic differences in self-perceived health in Estonia and Finland

Abstract: Self-perceived health was poorer in Estonia than in Finland, but Estonia shares with Finland a similar socioeconomic pattern of health. Further research is needed to monitor socioeconomic variations in health behaviour and mortality in both countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 25 publications
(50 reference statements)
7
19
0
Order By: Relevance
“…As shown in previous international studies, a higher SEP was related to better health [19, 20]. Adults with higher education [11, 21] and income [9, 10, 22] rated their health as good more often than people with lower education and income. Good SRH was more prevalent among employed adults when compared to respondents who were unemployed [2, 11].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…As shown in previous international studies, a higher SEP was related to better health [19, 20]. Adults with higher education [11, 21] and income [9, 10, 22] rated their health as good more often than people with lower education and income. Good SRH was more prevalent among employed adults when compared to respondents who were unemployed [2, 11].…”
Section: Introductionmentioning
confidence: 64%
“…Factors like gender, age, nationality, marital status, place of residence, education, employment status, occupation and income are viewed as determinants of health differences and SEP [10, 11]. As shown in previous international studies, a higher SEP was related to better health [19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies concerning self-rated health in Finland [25] and cross national comparisons [26,27] showed that self-perceived health was poorer in Estonia than in Finland. In both countries women with low education had poor self-rated health.…”
Section: Introductionmentioning
confidence: 99%
“…In both countries women with low education had poor self-rated health. In Estonia, but not in Finland economic inactivity was associated with poor self-rated health [27]. …”
Section: Introductionmentioning
confidence: 99%